Daytime variation in hepatitis C virus replication kinetics following liver transplant [version 2; referees: 4 approved, 1 approved with reservations] - Xiaodong Zhuang; Alvina G. Lai; Jane A. McKeating; Ian Rowe; Peter Balfe (Wellcome Open Research, 2018)
Background: There is a growing interest in the role of circadian regulated pathways in disease pathogenesis. Methods: In a cohort of hepatitis C virus (HCV) infected patients undergoing liver transplantation, we observed differences in early viral infection kinetics of the allograft that associated with the time of liver transplant. Results: A higher frequency of subjects transplanted in the morning showed a rebound in viral RNA levels (n=4/6) during the first week post-surgery. In contrast, no viral rebound was observed in seven subjects transplanted in the afternoon. None of the other parameters previously reported to influence viral replication in the post-transplant setting, such as donor age, cold-ischemia time and length of surgery associated with viral rebound. Conclusions: These observation highlights a role for circadian processes to regulate HCV infection of the liver and warrants further investigation.